A good way to remember this is to look at an example of why it works.
x^2 = xx
x^3 = xxx
(x^3)^2 = (xxx)(xxx) = x^6 = x^(2*3) = x^(3+3)
(x^2)^3 = (xx)(xx)(xx) = x^6 = x^(3*2) = x^(2+2+2)
(x^2)(x^3) = (xx)(xxx) = x^5 = x^(2+3)
You start with a bunch of x's multiplied together, and you count them. If you multiply by another bunch of x's (maybe a different length), you make a longer string of x's, and counting them is the same as adding the two original numbers.
Taking something to a power means repeatedly multiplying the same thing. So you put a bunch of identical strings of x's together, and since multiplication is repeated addition and the exponents add (repeatedly in this case), it is the same as multiplying the exponents together.
_________________
"A dead thing can go with the stream, but only a living thing can go against it." --G. K. Chesterton